El impuesto a los consumos especiales (I.E.C) de cigarrillos y cervezas, análisis de las principales reformas tributarias y su incidencia a nivel socioeconómico en el cantón Quito durante el período 2007-2012 - Benalcázar Monteros, Carina Elizabeth (2013)
Our study presents a brief history of taxes in Ecuador, the tax structure, definitions, elements and classification of taxes. It shows the study sources that were used to determine the tax changes reflected in the Tax Code, Law on Internal Taxation, Regulations for the Implementation of the Internal Tax Regime Law, Tax Equity Act and the Environmental Development Law and Optimization of State Revenue, It allow present the economic and social impact of the Special consumption Tax on producers and consumers of cigarettes and beer. The methodology used for the collection of information was through surveys to producers and consumers of cigarettes and beer, for further analysis. It teaches the socio-economic impact generated by the tax changes that has been generated by the Special Consumption Tax on cigarettes and beer, and survey information.